On Cardinal Numbers and Self Adjusting M−sets. A Mathematical Letter. - (:unkn) unknown (My University, 2012)
This is a technical letter where we outline certain considerations involving cardinal numbers. Notations and terminology follow similarly from our previous article[1]. The mechanistic approach to the logical development of arithmetic in our previous article had proven so useful, that we wish here to extend its application to cardinality. Our Approach involves a mechanistic approach similar to that of our previous article with no reference to formal set theory[2].
Keywords: African Research